Enhancing Business Education in Nigerian Secondary Schools: A Comprehensive Approach - Obiako, Eberechukwu Chiamaka (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Business education serves as a cornerstone for preparing students to navigate the complexities of modern economies and global workforce demands. In Nigeria, secondary schools play a critical role in equipping students with the foundational skills needed for entrepreneurial success, financial management, technological proficiency, and leadership. However, the current state of business education faces significant challenges, including outdated curricula, inadequate teacher training, limited resources, and a lack of integration with modern technological advancements. This article presents a comprehensive approach to enhancing business education in Nigerian secondary schools, identifying key areas for improvement such as entrepreneurship development, financial literacy, digital business, sustainability, and soft skills training. It advocates for the incorporation of global best practices, industry partnerships, and innovative teaching methods to address these challenges. Furthermore, it highlights the importance of STEM integration, cultural awareness, and leadership training as tools to empower students and foster economic development. By addressing systemic challenges such as resource disparities and the digital divide, this study underscores the need for a collaborative effort among educators, policymakers, and the private sector to revitalize business education in Nigeria. It proposes actionable strategies, including curriculum modernization, teacher empowerment programs, and monitoring frameworks to ensure sustained progress. Ultimately, this article envisions a future where business education becomes a transformative force in shaping Nigeria’s youth, driving economic growth, and fostering global competitiveness.